Exposure to air pollutants and the gut microbiota: a potential link between exposure, obesity, and type 2 diabetes. (2nd September 2020) - Bailey, Maximillian J.; Naik, Noopur N.; Wild, Laura E.; Patterson, William B.; Alderete, Tanya L.
ABSTRACT: Work has shown that increased exposure to air pollutants independently contributes to obesity and type 2 diabetes risk, yet the exact mechanisms underlying these associations have not been fully characterized. The current review summarizes recent findings regarding the impact of inhaled and ingested air pollutants on the gut microbiota. Animal and human studies provide evidence that air pollutants, such as particulate matter, nitrogen oxides, and ozone, have the potential to alter the gut microbiota. Further, studies suggest that such exposure-induced alterations to the gut microbiota may contribute to increased risk for obesity and type 2 diabetes through inflammatory pathways. Future work is needed to fully understand the complex interactions between air pollution, the gut microbiome, and human health. Additionally, advanced sequencing methods for gut microbiome research present unique opportunities to study the underlying pathways that link increased air pollution exposure with obesity and type 2 diabetes risk.